Case report: Chronic neutrophilic leukemia associated with monoclonal gammopathies. A case series and review of genetic characteristics and practical management - Vermeersch, Gaël; Delforge, Michel; Havelange, Violaine; Graux, Carlos; Michaux, Lucienne; Devos, Timothy (Frontiers in Oncology, 2022)
Chronic neutrophilic leukaemia (CNL) is a rare but potentially aggressive BCR-ABL1-negative myeloproliferative neoplasm, characterized by sustained mature, neutrophilic leukocytosis. The discovery of key driver mutations in the colony-stimulating-factor-3 receptor (CSF3R) gene resulted in updated World-Health-Organization (WHO)-diagnostic criteria in 2016. A significant number of CNL cases have been associated with plasma cell dyscrasias, predominantly multiple myeloma (MM) and monoclonal gammopathy of unknown significance (MGUS). Compared to pure CNL, mutated CSF3R is infrequently reported in CNL cases associated with monoclonal gammopathies (MG). Until now it remains unclear whether CNL and occurring plasma cell neoplasms are clonally related or CNL is developing secondary to the underlying dyscrasia. Due to its rarity currently no standard of care management exists for CNL and MG-associated CNL. In this case series we report the multi-centre experience of five MG-associated CNL cases with a median age of diagnosis of 69 years. 66% (n=3) showed predominance of lambda light chain expression. 80% (n=4) eventually evolved to MM and one CNL-MGUS patient developed secondary acute myeloid leukaemia (AML). Mutated CSF3R was present in the patient who developed AML but was absent in other cases. To assess possible associated genetic aberrations we performed recurrent analysis with next-generation sequencing (NGS). 40% (n=2) patients deceased with a median time of survival of 8 years after CNL diagnosis. 60% (n=3) are currently in follow up with no reoccurring leukocytosis. This case series, followed by a short review, provides a long-term clinical and genetic overview of five CNL cases associated with MG.